1998
DOI: 10.1063/1.366867
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency permeability of soft-magnetic Fe–Hf–O films with high resistivity

Abstract: A series of Fe–Hf–O films has been prepared by means of rf sputter deposition. The composition for optimal permeability was found to be Fe55Hf17O28. These films exhibit a combination of soft-magnetic properties (μ>103, Hc<50 A/m, μ0Ms⩾1.0 T) and a high resistivity (ρ>1 mΩ cm) after rapid thermal annealing in flowing argon at 400 °C in a dc magnetic field. The structure of the films consists of α-Fe nanocrystallites, randomly dispersed in an amorphous matrix. The amorphous phase is essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…The gyromagnetic factor γ is approximately 176 GHz/T [9], and the damping constant α is 0.015 corresponding to our thin film). As shown in Figure 5, the two experimental results agree with the theoretical one closely up to 6 GHz.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gyromagnetic factor γ is approximately 176 GHz/T [9], and the damping constant α is 0.015 corresponding to our thin film). As shown in Figure 5, the two experimental results agree with the theoretical one closely up to 6 GHz.…”
Section: Resultsmentioning
confidence: 99%
“…The complex permeability of thin film is measured by the two methods, and the theoretical result is also obtained from LandauLifshitz-Gilbert equation [9] (The saturation magnetization M s and anisotropy constant K u are measured as 1.41 × 10 6 A/m, and 1500 J/m 3 , respectively. The gyromagnetic factor γ is approximately 176 GHz/T [9], and the damping constant α is 0.015 corresponding to our thin film).…”
Section: Resultsmentioning
confidence: 99%
“…Earlier Huijbregtse et al 9 reported on the frequency dependence of the magnetic permeability of a thick FeHfO film and interpreted the behavior in terms of combined eddy current shielding and ferromagnetic resonance ͑FMR͒ effects. In the present article we present a more detailed analysis including the thickness dependence.…”
Section: Introductionmentioning
confidence: 99%
“…9 Among these materials there is particular interest in FeHfO not only for its magnetoresistance but also for its soft magnetic properties. [10][11][12] In this article we report on the observed TMR in reactive sputter deposited FeHfO and FeHfSiO thin films. We will focus on the temperature dependence of the TMR and resistivity which has not been studied in great detail so far and this yields additional insight into the mechanisms for spindependent conductivity.…”
Section: Introductionmentioning
confidence: 99%